Performance Analysis for Cooperative Communication System with QC-LDPC Codes Constructed with Integer Sequences. (9th February 2015) - Zhang, Yan; Yang, Feng-fan; Song, Weijun
Abstract : This paper presents four different integer sequences to construct quasi-cyclic low-density parity-check (QC-LDPC) codes with mathematical theory. The paper introduces the procedure of the coding principle and coding. Four different integer sequences constructing QC-LDPC code are compared with LDPC codes by using PEG algorithm, array codes, and the Mackey codes, respectively. Then, the integer sequence QC-LDPC codes are used in coded cooperative communication. Simulation results show that the integer sequence constructed QC-LDPC codes are effective, and overall performance is better than that of other types of LDPC codes in the coded cooperative communication. The performance of Dayan integer sequence constructed QC-LDPC is the most excellent performance.